Передумови розвитку наземної фотоелектрики у 70-х рр. ХХ ст. - Хрипунова, Аліна Леонідівна (Національний технічний університет України "Київський політехнічний іститут" ім. Ігоря Сікорського, 2015)
У статті розглянуто історичні передумови, які призвели до світової енергетичної кризи у 70-х рр. ХХ ст.

The article researches the historical background that led to the global energy crisis in 70 years of the 20th ct.: extensive economic development, decolonization oil extraction, failure by the United States gold backing from the US dollar, the embargo on the oil supply. In the United States and European countries were initiated different projects to ensure energy independence. In the US in 1974 was funded by the nation’s largest program in the field of photovoltaics. The positive experience of the program has shown that using solar energy can solve energy problems. Based on the positive experience of the United States in five years in Germany begins a state program for the development of photovoltaics. The presence of German industrial companies that produce solar cells based on monocrystalline silicon for space applications and scientific schools in the field of photovoltaics, allowed to develop evidence-based national programs. Development of the photovoltaic contributed to the diversification of research that focused not only on the development of structural and technological solutions of crystalline silicon solar cells, but also on optimization the technology of thin-film solar cells based on cadmium sulfide and amorphous silicon.
The historical background of the photovoltaics development in 1970’s
Keywords: екстенсивний розвиток економіки; еколонізація видобутку нафти; енергетична криза; відновлювані екологічно чисті джерела енергії; extensive economic development; decolonization oil; energy crisis; photovoltaics